Phosphorylated STAT3 as a potential diagnostic and predictive biomarker in ALK- ALCL vs. CD30high PTCL, NOS - Xiang, Chenxi; Wu, Wanna; Fan, Meiting; Wang, Zhen; Feng, Xiaoli; Liu, Cuiling; Liu, Jia; Liu, Guangzhen; Xia, Lei; Si, Haipeng; Gu, Ying; Liu, Nian; et al. (Frontiers in Immunology, 2023)
Aims: The differential diagnosis between ALK-negative anaplastic large cell lymphoma (ALK- ALCL) and peripheral T-cell lymphoma, not otherwise specified (PTCL, NOS) with high expression of CD30 (CD30high) are essential. However, no reliable biomarker is available in daily practice except CD30. STAT3 is characteristically activated in ALCL. We aimed to investigate whether the status of STAT3 phosphorylation could help the differential diagnosis. Methods: The status of phosphorylation of STAT3 was examined using two antibodies against pSTAT3-Y705 and pSTAT3-S727 by immunohistochemistry in ALK+ ALCL (n=33), ALK- ALCL (n=22) and PTCL, NOS (n=34). Ten PTCL, NOS with diffuse CD30 expression were defined as CD30high PTCL, NOS. Flowcytometric analysis were performed to evaluate the expression of pSTAT3-Y705/S727 in PTCL, NOS (n=3). Results: The median H-scores of pSTAT3-Y705 and S727 were 280 and 260 in ALK+ ALCL, 250 and 240 in ALK- ALCL, and 45 and 75 in CD30high subgroup, respectively. Using H score of 145 as the cutoff value, pSTAT3-S727 alone distinguished between ALK- ALCL and CD30high PTCL, NOS with a sensitivity of 100% and specificity of 83%. Additionally, pSTAT3-S727, but not pSTAT3-Y705, was also expressed by background tumor-infiltrating lymphocytes (S727TILs) in PTCL, NOS. PTCL, NOS patients with high S727TILs H score had a favorable prognosis than those with no TILs (3-year OS rate: 43% vs. 0, p=0.013) or low S727TILs (3-year OS rate: 43% vs. 0, p=0.099). Flowcytometric analysis revealed that of the three patients investigated, two had enhanced pSTAT-S727 signals in neoplastic cell populations, and all three patients were negative for pSTAT3-Y705 expression in both tumor cells and background lymphocytes. Conclusions: pSTAT3-Y705/S727 can be used to help distinguish ALK- ALCL from CD30high PTCL, NOS and pSTAT3-S727 expression by TILs predicts the prognosis of a subset of PTCL, NOS.